Māori Participation - Sullivan, Kaapua (New Zealand government & politics, 2010)
Keywords: Elections – New Zealand; New Zealand – Politics and government – 1972-; Political parties – New Zealand; Proportional representation – New Zealand; Representative government and representation – New Zealand

Māori Party - Smith, Kaapua (New Zealand Government & Politics, 2010)
Keywords: Elections – New Zealand; New Zealand – Politics and government – 1972-; Political parties – New Zealand; Proportional representation – New Zealand; Representative government and representation – New Zealand

The Maori Party - Katene, Rahui (Key to victory : the New Zealand general election of 2008, 2010)
Keywords: Coalition governments – New Zealand; Elections – New Zealand; Key; John; 1961-; New Zealand – Politics and government – 21st century; New Zealand Parliament – Elections; 2008; Political campaigns – Press coverage – New Zealand; Proportional representation – New Zealand; Voting – New Zealand

A Genealogy of Indigenous Resistance - Hokowhitu, Brendan (Indigenous Identity and Resistance: Researching the Diversity of Knowledge, 2010)
Brings together the work of scholars working in Canada, New Zealand and the Pacific in an exploration of the multifaceted nature of indigenous studies and the concept of indigenous studies as an academic discipline. Source: National Library of New Zealand Te Puna Matauranga o Aotearoa, licensed by the Department of Internal Affairs for re-use under the Creative Commons Attribution 3.0 New Zealand Licence.
Keywords: activism; ethnic identity; government; iwi taketake; land march; parliament; rangahau māori; resistance; tāngata whenua

The Foreshore and Seabed Act: Five years on, where to from here - Whare, Tracey (Māori and the environment: kaitiaki, 2010)
Keywords: citizenship; environment; environmental policy; kaitiakitanga; print only; social life and customs; taiao; water management